2006
DOI: 10.1007/s00125-006-0359-4
|View full text |Cite
|
Sign up to set email alerts
|

Plasma N-terminal pro-B-type natriuretic peptide and mortality in type 2 diabetes

Abstract: Aims/hypothesis Raised N-terminal pro-B-type natriuretic peptide (NT-proBNP) is associated with a poor cardiac outcome in non-diabetic populations. Elevated NT-proBNP predicts excess morbidity and mortality in diabetic patients with an elevated urinary albumin excretion rate. This study investigated the prognostic value of NT-proBNP in a cohort of type 2 diabetic patients. Subjects, materials and methods In a prospective observational follow-up study, 315 type 2 diabetic patients with normoalbuminuria (n=188),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
82
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(93 citation statements)
references
References 34 publications
6
82
3
Order By: Relevance
“…This finding may seem at odds with the reported data in the literature and in particular with the only known to us study on mortality risk, which was performed in type 2 diabetic patients (26).…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…This finding may seem at odds with the reported data in the literature and in particular with the only known to us study on mortality risk, which was performed in type 2 diabetic patients (26).…”
Section: Discussioncontrasting
confidence: 80%
“…One limitation of our study was not to have investigated a subclinical left ventricular hypertrophy or ischemic coronary disease (28,29). However, also the above-mentioned study of Tarnow et al (26) did not carry out investigations beyond at resting electrocardiogram which has a notoriously low sensitivity.. However, since BPN has a strong prognostic power, an abnormal value of it could be the reason for starting with a more accurate heart diagnostic evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic information provided appears to be incremental to that derived from established risk factors. There are, however, relatively few data assessing the ability of BNP and NT-proBNP to predict cardiovascular outcomes in patients with type 2 diabetes (14,15) and no prior studies that assess the ability of these markers to reclassify the risk of individual patients.…”
mentioning
confidence: 99%
“…Others have found, however, that NT-proBNP also strongly predicts all-cause and CVD-related mortality in individuals with type 2 diabetes mellitus. 26 Several previous studies have found that higher levels of NT-proBNP predict cardiovascular events in patients with heart failure, in older individuals, and in patients on dialy- Adjusted RH of any cardiovascular event, by NTproBNP category for selected subgroups (adjusted for age, sex, baseline GFR, systolic and diastolic blood pressure, urinary sodium-potassium ratio, non-HDL cholesterol, abnormal ECG, body mass index, and randomization group assignment). †Pro-teinuria defined as urinary protein-creatinine ratio Ͼ0.22.…”
Section: Discussionmentioning
confidence: 99%